Hot-medium effects on [upsilon] yields in pPb collisions at √sNN=8.16 TeV - Dinh, Viet Hung; Hölck, Johannes; Wolschin, Georg (Physical review, 2019)
The respective contributions of cold-matter and hot-medium effects to the suppression of Υ(1S) and Υ(2S) mesons in pPb collisions at energies reached at the CERN Large Hadron Collider (LHC) are investigated. Whereas known alterations of the parton density functions in the lead nucleus and coherent parton energy loss account for the leading fraction of the modifications in cold nuclear matter (CNM), the hot-medium (quark-gluon plasma, QGP) effects turn out to be relevant in spite of the small initial spatial extent of the fireball. We compare our transverse-momentum-, rapidity-, and centrality-dependent theoretical results for the Υ suppression in pPb collisions at a center-of-mass energy of √sNN=8.16TeV with recent LHCb and preliminary ALICE data from the LHC. Both cold-matter and hot-medium effects are needed to account for the data. The initial central temperature of the fireball is found to be T0≃460MeV, but depends on the bottomonium formation time.
Im Titel ist "Ypsilon" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 06.02.2020